Crisis Liquidity and Financial Inclusion: Revenue Performance of KCA and KREASI - Yayu Rakkang; Fahruni Khaerunnisa (Jurnal Riset Akuntansi, 2025)
Abstract. The COVID-19 pandemic disrupted global financial services and increased demand for rapid liquidity among low-income communities. This study examines the performance of a state-owned pawn institution in Makassar across two flagship products, namely the pawn-based Kredit Cepat Aman (KCA) and the fiduciary installment Kredit Angsuran Sistem Fidusia (KREASI), before (2019) and during (2020) the pandemic. Using a comparative longitudinal design, the analysis draws on revenue data from ten branches. The results reveal a clear divergence in product performance. Revenue from the pawn-based product increased significantly, reflecting customers’ preference for fast liquidity supported by collateral and simple procedures. In contrast, revenue from the fiduciary installment product declined overall, with limited growth observed in only a few branches. Substantial variation across branches was also evident, with branches located in commercial centers demonstrating greater resilience than those in peripheral areas. These findings indicate that adjusting product portfolios to local shock profiles—by maintaining fast, collateral-based lending channels and recalibrating installment financing in line with recovery dynamics—can strengthen financial inclusion and institutional resilience. The study contributes to the literature on microfinance performance during crises and highlights the importance of contextual risk management in sustaining financial services under conditions of economic disruption.